2019
DOI: 10.1186/s12864-019-6177-0
|View full text |Cite
|
Sign up to set email alerts
|

Organ transcriptomes of the lucinid clam Loripes orbiculatus (Poli, 1791) provide insights into their specialised roles in the biology of a chemosymbiotic bivalve

Abstract: BackgroundThe lucinid clam Loripes orbiculatus lives in a nutritional symbiosis with sulphur-oxidizing bacteria housed in its gills. Although our understanding of the lucinid endosymbiont physiology and metabolism has made significant progress, relatively little is known about how the host regulates the symbiosis at the genetic and molecular levels. We generated transcriptomes from four L. orbiculatus organs (gills, foot, visceral mass, and mantle) for differential expression analyses, to better understand thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 98 publications
0
19
0
Order By: Relevance
“…In Thau lagoon at this period, the main primary production bloom occurs (Bec et al 2005), and a possible hypothesis is that mucocytes may be involved in the heterotrophic nutrition of the host as is the case for other bivalves; one of the main roles attributed to the mucus secreted by mucocytes concerns particle-feeding processes (Beninger and St Jean 1997). Another hypothesis concerns host immunity, as gills and mucus are greatly involved in this function (Allam and Pales-Espinosa 2016; Yuen et al 2019). Moreover, since 2008, massive spring mortality has been regularly recorded in oysters in the Thau lagoon (Pernet et al 2012), involving a community of pathogenic microorganisms (Alfaro et al 2019) that may trigger Loripes' defence systems.…”
Section: Sexually Determined Mucocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Thau lagoon at this period, the main primary production bloom occurs (Bec et al 2005), and a possible hypothesis is that mucocytes may be involved in the heterotrophic nutrition of the host as is the case for other bivalves; one of the main roles attributed to the mucus secreted by mucocytes concerns particle-feeding processes (Beninger and St Jean 1997). Another hypothesis concerns host immunity, as gills and mucus are greatly involved in this function (Allam and Pales-Espinosa 2016; Yuen et al 2019). Moreover, since 2008, massive spring mortality has been regularly recorded in oysters in the Thau lagoon (Pernet et al 2012), involving a community of pathogenic microorganisms (Alfaro et al 2019) that may trigger Loripes' defence systems.…”
Section: Sexually Determined Mucocytesmentioning
confidence: 99%
“…A similar temporal fluctuation in symbiont abundance, a proxy for bacteriocytes, was also observed in Thysirids according to season (Laurich et al 2015). More recently, the postulate of the heterotrophic nutrition of Loripes has been strengthened by the ability of this host's symbionts to digest complex polysaccharides (Yuen et al 2019), typically found in marine phytoplankton (Mühlenbruch et al 2018). In suspension-feeding bivalves, heterotrophic nutrition is related to the ability of the gills to collect and process particulate organic matter via mucocytes' acid secretion from the anterior part of the gill (Beninger and Dufour 1996;Beninger and St Jean 1997;Ward and Shumway 2004).…”
Section: Sexually Determined Mucocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the roles of microbiomes is one that appears to be particularly broad in terms of the number and span of eukaryotic host clades for which it has been documented: nutrition (Akman Gündüz & Douglas, 2009;Graf, 1999;Semova et al, 2012;C. Wilkinson & Cheshire, 1990;Yuen et al, 2019;Zimmer & Bartholmé, 2003). The specific mechanisms by which microbes enable the provision of nutrients for their hosts differs among symbioses and is largely contingent on the trophic strategies of the microbes; fermentative gut prokaryotes of ruminants break down plant material that is undigestible by the host (Yeoman & White, 2014), photoautotrophic dinoflagellates use light and host-derived CO 2 to produce sugars for zooxanthellate hermatypic corals (Davy et al, 2012); and rhizosphere bacteria perform nitrogen fixation to convert atmospheric nitrogen (N 2 ) to ammonia (NH 3 ), a biologically available nitrogen source for legumes (Kuypers et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These processes have been demonstrated experimentally to have a positive effect on host sponge fitness, as is the case with photosynthesis (C. J. Freeman & Thacker, 2011), have strong correlative evidence for supplementing host nutrition, as has been observed in methanotrophic symbionts (Rubin-Blum et al, 2019), or likely affect sponge fitness positively based on the physiological exchanges documented in other host clades that possess symbionts performing similar biochemical functions. These include the sulfur oxidizing symbionts of lucinid clams (Yuen et al, 2019) and vestimentiferan tube worms (Stewart & Cavanaugh, 2006), and the aforementioned examples of the nitrogen fixation in legumes (Kuypers et al, 2018) and fermentation in ruminants (Yeoman & White, 2014).…”
Section: Introductionmentioning
confidence: 99%